2018
DOI: 10.3389/fnagi.2018.00066
|View full text |Cite
|
Sign up to set email alerts
|

Catalpol Inhibits Amyloid-β Generation Through Promoting α-Cleavage of APP in Swedish Mutant APP Overexpressed N2a Cells

Abstract: Amyloid-β (Aβ) peptides play a crucial role in the pathogenesis of Alzheimer’s disease (AD), due to its neurotoxicity. Thus, blocking Aβ generation and aggregation in the brain has been realized as an efficient way for the prevention of AD. The natural product catalpol, isolated from Rehmannia glutinosa, has shown neuroprotective activities through inhibiting soluble Aβ production, degrading Aβ peptide, and attenuating Aβ toxicity and neuroinflammatory responses. In the present study, we aimed to evaluate whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…Aβ levels were found to reduce after treatment with catalpol however, APP, β-secretase, and γ-secretase complex expression levels were found to be unaffected by catalpol. This indicates that the inhibition of Aβ by catalpol is due to a non-amyloidogenic pathway and further proven by the increase in non-amyloidogenic process-related proteins such as α-secretase (ADAM10) and its proteolytic by-products, sAPPα and C83 via ERK/CREB signaling [27]. While experimental studies indicate the potential for catalpol as a treatment for AD through improving cholinergic pathway and inhibiting aging progression in experimental animal model, there is yet to be any clinical findings for substantiating this claim.…”
Section: Alzheimer's Diseasementioning
confidence: 93%
See 1 more Smart Citation
“…Aβ levels were found to reduce after treatment with catalpol however, APP, β-secretase, and γ-secretase complex expression levels were found to be unaffected by catalpol. This indicates that the inhibition of Aβ by catalpol is due to a non-amyloidogenic pathway and further proven by the increase in non-amyloidogenic process-related proteins such as α-secretase (ADAM10) and its proteolytic by-products, sAPPα and C83 via ERK/CREB signaling [27]. While experimental studies indicate the potential for catalpol as a treatment for AD through improving cholinergic pathway and inhibiting aging progression in experimental animal model, there is yet to be any clinical findings for substantiating this claim.…”
Section: Alzheimer's Diseasementioning
confidence: 93%
“…In aged rats, catalpol increased hippocampal levels of the presynaptic proteins, synaptophysin and growth-associated protein (Gap-43) which are markers of neuroplasticity [26]. Wang et al [27] confirmed the neuroprotective effects of catalpol via a novel non-amyloidogenic pathway. Swedish mutant amyloid precursor protein (APP) overexpressed N2a cells that enhances the production of Aβ were treated with catalpol.…”
Section: Alzheimer's Diseasementioning
confidence: 97%
“…[ 30,31 ] Thus, the APP processing shifts from β‐secretase to α‐secretase contributes to the suppression of toxic Aβ 1‐40/42 production. [ 32 ] Binding of redox‐active metal ions on the N‐terminal metal‐binding domains of Aβ is considered more toxic for the induction of ROS production, while ROS, in turn, impair Aβ clearance by the low‐density lipoprotein receptor‐related protein (LRP1) due to its oxidation. [ 1 ] Besides, we recently reported that H 2 O 2 , a vital member of ROS family, could also induce β‐secretase expression and reduced α‐secretase expression in neuronal cells.…”
Section: Discussionmentioning
confidence: 99%
“…SIRT1 has a myriad of neuroprotective activities but it is known to upregulate ADAM10 expression through retinoid acid receptors [85,86]. A good number of compounds with varying chemical backbones also enhance non-amyloidogenic processing of APP with mechanisms that have not been clearly deciphered [87][88][89][90][91][92][93][94], and some of which may involve ADAM10 activation. ADAM10's activity on APP is also known to be dependent on membrane lipids factors, such as transient exposure of the negatively charged phospholipid phosphatidylserine (PS) [95], as well as O-GlcNAcylation of APP [96].…”
Section: Multiple Ways Of Modulating α-Secretase-based App Processingmentioning
confidence: 99%